Quantitative Methods in Scientific Research - Barella, Yusawinur; Fergina, Ana; Mustami, Muhammad Khalifah; Rahman, Ulfiani; Alajaili, Hetham M Alaitori (Universitas Tanjungpura, 2024)
The description of quantitative research is an essential part of a study that uses research methods based on numbers and statistics to obtain, analyze, and explain data. This research aims to gain a deeper understanding of the quantitative research methods, types of research in quantitative research, procedures, and data measurement in quantitative research. The data was collected through a literature review. The results of this study are expected to provide a strong understanding of quantitative research methods and to make a significant contribution to the development of scientific knowledge and decision-making in various fields.